A Study of Nilofar Iqbal's Short Stories Collection “Siah Sona” - Kallu, Parveen; Rahman, Ata Ur; Khan, Javez (sourcecoder, 2024)
"Siah Sona" is Nilofar Iqbal's third and so far his last collection of fiction. Some of his fiction in this collection are reminiscent of his first two fiction collections in terms of technique and subject matter, and some of the fiction are of new technique and unique subject matter. But the flow of style is in all three collections. Her fiction is neither original style nor weighed down by heavy techniques. She chooses this specific style for her fiction writing. That is closer to their mood. In this period when Urdu fiction has explored many possibilities. It is a challenge to make a name in the fiction of narrative tradition and realistic mood, but to get a high position. But Nilofar Iqbal has done her job well.